Pengaruh Kualitas Layanan Livin By Mandiri Terhadap Kepuasan dan Loyalitas Nasabah PT Bank Mandiri Di Banjarmasin Pada Masa Pandemi Covid-19 - Olivia Januarti; Suyatno Suyatno (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
ABSTRACT The research method used is positivistic, explanatory causality, data collection using a survey method with a sample size of 225 customers using Livin by Mandiri services in 5 sub-districts in Banjarmasin Kota. Data collection was carried out using the e-survey method. The google form questionnaire was distributed via facebook. The data analysis technique uses path analysis techniques. Data calculation using the SPSS Version 26 application.The results of the study prove that the service quality of Livin by Mandiri had a direct and significant positive effect on Customer Satisfaction and Loyalty. Customer satisfaction directly has a significant positive effect on loyalty. Customer satisfaction mediates a significant positive on the effect of Livin by Mandiri's service quality on customer loyalty using the application. Keywords: Livin by Mandiri, Service Quality, Satisfaction, Loyalty, Covid-19 Pandemic